Endovascular or open surgical treatment of high-risk patients with infrainguinal peripheral arterial disease and critical limb ischemia - Dragan Totić; Vesna Ðurović Sarajlić; Haris Vranić; Amel Hadžimehmedagić; Nedžad Rustempašić; Muhamed Djedović; Haris Vukas; Alen Ahmetašević (Medicinski glasnik, 2020)
Aim: To determine preferable type of treatment in our clinical circumstances by following two groups of patients with critical limb ischemia (CLI), who were treated endovascularly and surgically. Methods: Research was carried out in the form of a prospective study of 80 patients with CLI and TransAtlantic Inter-Society Consensus (TASC) C or D type of arterial disease, with American Society of Anesthesiology (ASA) class III risk, who were randomly divided in two groups as per the treatment they received, surgical and endovascular. Patients were followed during 28 months using clinical examination and Duplex Ultrasound (DUS) in accordance with prescheduled control visits. Results: There was a statistical difference between surgical and endovascular group in two years patency (82.5% vs. 55%; p=0.022) but it did not result in the difference in amputation free survival (AFS) (95% vs. 85%; p=0.171) or two-year freedom from major adverse limb events (MALE) (87.5 vs. 77.5; p=0.254). Also, there was no difference in the overall survival of patients (100% vs. 97.5%; p=0.317). Conclusion: Initial endovascular treatment is a preferred form of the treatment for selected patient population.
Keywords: amputation-free survival; endovascular procedure; infrainguinal bypass; patient survival critical limb ischemia; endovascular; peripheral arterial disease; surgical